POLITICAL RELATION BETWEEN TAIWAN AND CHINA AFTER THE SELECTED OF THE NEW PRESIDENT - Russel Ong; Argo Victoria Ong (UNISSULA, 2018)
Tsai Ing-Wen (Tsai) was elected Taiwan's first female president after succeeding won the general election with 56.1% of votes. His victory is expected to push a new round of independence efforts Taiwan from China, and can lead to China's instability. Transition the politics that the two regions will pass into global political developments relating to economic and trade cooperation that has been carried out. Time ahead of China and Taiwan will be tested by peaceful means or hostility completely dependent on Tsai's own choice. Even though Indonesia is not intertwined diplomatic relations with Taiwan, relations between the two countries are expected to continue increasing given the ongoing economic and trade cooperation enhancement.